RESTORATION OF MUNICIPAL WATERWORKS (PDAM) SYSTEM FOR PUBLIC COMPLAINTS - Lukita, Farhan Zerlinda; Khumayah, Siti; Rahmayanti, Rahmayanti (Cahaya Ilmu Bangsa, 2025)
The public service system, especially Tirta Jati Cirebon Regency Municipal Waterworks, is a service provided by a Regional-Owned Enterprise that facilitates the provision of clean water for the people of Cirebon Regency. This study aims to investigate the service system and public complaints at Tirta Jati Cirebon Regency Municipal Waterworks, focusing on public services in the context of clean water availability. Various studies have been conducted on customer satisfaction of Tirta Jati Municipal Waterworks, with the approach and theory used is the theory of public services according to Parasurarman which includes five indicators such as Tangible, Reliability, Responsiveness, Assurance, and Empathy. Although Tirta Jati Cirebon Regency Municipal Waterworks has provided clean water services, there are still shortcomings felt by the community such as the lack of proficiency from employees about customer needs. Therefore, this study aims to explore the influence of these indicators on the level of customer satisfaction with Municipal Waterworks services. This study also examines the customer complaint and grievance management system implemented by Tirta Jati Municipal Waterworks, and how it affects service effectiveness and responsiveness to community needs. Using public service theory, this research is expected to contribute to the development of better policies in improving the quality of Tirta Jati services and the fulfillment of clean water needs in Cirebon Regency.